Food forensics the hidden toxins lurking in your food and how you can avoid them for lifelong health - Adams, Mike 1967 (BenBella Books, Inc., 2016)
"What's really in our food? Award-winning investigative journalist and activist Mike Adams, the "Health Ranger," is founder and editor of NaturalNews.com, the number one most visited natural health website in the world. With more than 5 million unique visitors a month, NaturalNews.com is the trusted source for health information for countless readers. Now, in an industry first, Adams and his team put the things we eat every day under the microscope to expose the hidden truth about the contaminants in our foods. Through incredible high-resolution microscope images, Food Forensics shows us what we can't see on our own and test levels of lead, arsenic, cadmium, mercury, and more in common foods and additives, from cereals, soups, and other pre-packaged meals to fast food and medicinal herbs. Adams's tests reveal the differences between organic and non-organic foods, GMO and non-GMO certified foods, and more, plus which foods and brands are the cleanest. All test results adhere to EPA-approved lab protocols, exceeding even Consumer Reports levels of accountability, and have been verified by a third-party university lab. Food Forensics discloses how food contamination happens and why it matters, and provides valuable information on how you can protect yourself. If the FDA and the USDA won't safeguard us from food contamination, the Health Ranger will"